Effects of macro-circulation on local climatic conditions of plant development - Mika János; Molnár József; Молнар Йосип; Tar Károly (Elsevier Ltd., 2005)
Abstract. Agricultural or ecological impact studies, related to future climate changes, require highly resolved meteorological input data both in space and time. Since present climate models can not fulfill this requirement, gaps between the necessary and available resolution, are filled by downscaling. A possible way to downscale GCM-output fields into regional climate scenarios can be to consider the changes in the frequency distribution of model-generated macro-circulation types and to combine them with conditional climatology of each macro-type. This approach can be successful, if a great part of local climate anomalies is connected to frequency anomalies of the macro-types. To test this assumption, a diagnostic method for separation of the local climate anomalies into circulation and non-circulation (physical) factors, allowing a mixed term, is developed, applying the subjective classification of pressure patterns by Péczely (1957). Results for monthly and seasonal anomalies of precipitation and temperature are presented for Debrecen, Hungary (47°N, 21°E). The investigated period is 30 years from 1966 to 1995. The main feature of the results is the secondary role of the macro-circulation factor. This conclusion is formulated from the comparison of contributions by these terms to moderate and extreme anomalies; to the standard deviation and to long-term variations; and also from the correlation between the three terms and their sum, i.e. the monthly anomaly. It is impossible, however, to consider this circulation term as the maximum information contained by a series of macro-types, because the succession of macro-types and conditional relation of the local weather on different days of a given type is not taken into account by the given separation. On the other hand, the circulation term exhibits fair statistical relation to the physical term and also to the whole anomaly in many cases, which is promising considering further improvement of this approach to downscaling based on frequency of macro-synoptic types.
Keywords: climate change; statistical downscaling; circulation types; weather generator; impact